O Jingle como identidade sonora de uma marca - Cereja, Samuel (Universidade do Vale do Rio dos Sinos, 2021)
This research investigates the responsibilities of the sound as a representative of a brand, conveying concepts and feelings to its consumers. Theories about brand, brand identity, musical structure and history of the sound are analyzed. This seeks to identify how the concept and identity of a brand are translated by the sound design of a jingle. The data are investigated through qualitative research in the form of a single case study. The Gasperin Pilatti Construções jingle is analyzed, identifying which were the strategic points used for its creation, in order to direct it efficiently to the company's public. As a result, it is realized that the function of the jingle is primarily to serve as a marketing reference for a brand through a sound stimulus, as well as to establish a relationship between the brand and the listener, through a value proposal that encompasses functional and emotional benefits.
Keywords: Som; Marca; Identidade; Jingle; Sound; Brand; Identity